Prejudice and discrimination in the everyday life of same-sex couples raising children - Tombolato, Mário Augusto (2018)
The present study investigated the experiences of prejudice and discrimination in the everyday lives of five same-sex couples raising children. Data were collected using a questionnaire and an interview and were analyzed by thematic analysis. Participants attributed meanings to their experiences of being homoparental families: they assumed their social role as they managed to develop their own conjugality and parental projects in the struggle within a social context permeated by the hegemony of heteronormative values. The participants experienced prejudice related to their lifestyle and attained parenthood status, challenging social norms and gender stereotypes. However, it was also found that attitudes of willingness and perseverance in their fight for their rights proved to be protective measures against prejudice and social intolerance. A limited number of studies have examined the prejudice and discrimination towards same-sex families in Brazil; therefore, there is a need for greater visibility and further discussion about this phenomenon.